Pengaruh Keterampilan Kerja dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan pada PT. Wahana Lestari Makmur Sukses Musi Banyuasin - Azima, Khuluqon; Lestari, Marjiyanti (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to know and describe the picture of work skills, work environment and work productivity of employees at PT. Wahana Lestari Makmur Success. To determine and analyze the effect of work skills and work environment on employee work productivity partially at PT. Wahana Lestari Makmur Success. To determine and analyze the effect of work skills and work environment on employee work productivity simultaneously at PT. Wahana Lestari Makmur Success. The research methodology used is qualitative descriptive analysis method and quantitative, the type of data used is primary data with questionnaire questionnaires. The analysis method used multiple linear regression analysis. This study used a population of 50 respondents. Hypothesis testing was performed using statistical f test and statistical t test. PT. Wahana Lestari Makmur Sukses was established in 2009 which has a business license for the utilization of timber forest products in industrial plantation forests that have a land area of 14,010 hectares in Musi Banyuasin Regency, South Sumatra Province. The company's production is to produce the largest and leading acacia tree in Indonesia. Based on the results of the study, the average answer score of 215.8 means that work skills are valued very high by employees, the average score of respondents' answers is 215.5 means that the work environment is rated very high by employees. The average score of respondents' answers of 209.8 means that work productivity is rated high by employees. The conclusion in this study is that work skills and work environment together have a significant effect on employee work productivity at PT. Wahana Lestari Makmur. Work skills have a positive effect on employee productivity at PT. Wahana Lestari Makmur, and the work environment positively affect the work productivity of employees at PT. Wahana Lestari Makmur. Employee work productivity was able to explain the variables of work skills and work environment by 66.80%, and the remaining 33.20% was explained by other variables outside the study.